(untitled) (International Journal of Food and Nutritional Sciences, 2026)
This paper talks about Karnad’s idea in folklore through the ray of prism. It refracts the desire, identity and fidelity in the play of Nagamandala and Hayavadana. In Nagamandala’s plot was Rani whose life was changed because of fate, when the curry was supposed to eaten by her husband but she gets terrified and pours it into the cobra hill. Here happens the intervention of the fate, the curry was tasted by the cobra who can change his from. In Hayavadana it’s an exact opposite. Where Padmini life starts with love but turns to love triangle. She finds it difficult to choose between her husband or his friend. The main character Hayavadana who happens to be half human and half horse. He becomes complete celestial divine white horse. The play ends with wholeness. This paper talks about how Karnad’s re-figures the idea and perspective of how our dysfunctionala society and their views. Allways the ladies of all the plots are sidelined but in Karnad’s play he always puts women in center. He talks about the instability of human mind by human it also includes women and their thinking too.